Literature Review of The use of Islamic Educational Games to Increase Interest in Learning and Understanding Islamic Teachings in Children - Al-Ghifari, Dimas; Koderi, Koderi; Jatmiko, Agus; Mustofa, Ihsan (Jurnal Multidisiplin Indonesia, 2024)
Islamic religious education in children is an important aspect in the formation of religious values and understanding from an early age.  However, teachers and parents often face challenges in attracting children's interest in learning and effectively conveying Islamic teachings.  In this context, the use of Islamic educational games promises an innovative approach to increase children's interest in learning and understanding Islamic teachings.  This article explores the potential use of Islamic educational games as an effective learning tool in the context of children's religious education.  By integrating Islamic values into the game, Islamic educational games are able to provide a fun learning experience while strengthening the understanding of religious teachings.  Through a theoretical approach and practical implementation, this article presents arguments that support the use of Islamic educational games as an effective means of improving learning and understanding of Islamic teachings in children.